Silybin Attenuates Neurobehavioural Impairments and Secondary Brain Damage Following Traumatic Brain Injury in Mice - Bhardwaj, Hemlata (Scripta Medica, 2026)
Background/Aim: Traumatic brain injury (TBI) is a neurodegenerative disorder resulting in temporary or permanent impairment of cognitive, physical and psychosocial functions. Presently no treatment is available to overcome TBI. Flavonoids can be utilised for treatment of TBI due to their anti-oxidant and anti-inflammatory potential. Aim of this study was to investigate the neuroprotective potential of silybin against secondary cascade of TBI. Methods: TBI induced by weight drop model of trauma has been utilised to assess the neuroprotective effect of silybin at the doses 50 mg/kg and 100 mg/kg in mice. After 30 min of injury, silybin was administered. The effect of silybin was observed on neurobehaviour (Morris’s water maze test, beam walk and beam balance), blood brain barrier permeability (BBB), brain oedema and mitochondrial dysfunction after 24 h and 21 days of drug administration. The study of interaction of silybin with N-methyl-D-aspartate receptors (NMDARs) by using PDB: 3QEL was evaluated by molecular docking. Results: Silybin significantly improved the neurological behaviours such as motor coordination and learning and memory. Silybin significantly decreased the BBB permeability, brain oedema and mitochondrial dysfunction. Molecular docking studies showed the significant interactions of silybin with target residues MET 207, THR174, TYR175, PHE 176, PRO177, GLU236,THR233, GLU106, ALA107, GLN110, ASP136, ALA135, MET134 of PDB: 3QEL.Conclusion: Silybin provides novel insights into the neuroprotective and therapeutic potential for TBI.